2002
DOI: 10.1007/bf02376057
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport and solid state battery studies on a new silver molybdate superionic glass system: x[0.75AgI: 0.25AgCl]: (1-x)[Ag2O: MoO3]

Abstract: on the OCC and the results have been discussed on the basis of theoretical models suggested for superionic glasses. In addition to this, solid state batteries were fabricated using OCC as electrolyte and discharge characteristics were studied under varying load conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Also, a gradual weight loss is observed till 300 C, which may be due to the condensation of hydroxyl groups. The DTA profiles for these glasses are consistent with [23,24]. On the basis of this observation, it is identified that endothermic peak appears between 95 and 120 C, which represents the glass transition (T g ).…”
Section: Thermal Analysissupporting
confidence: 61%
“…Also, a gradual weight loss is observed till 300 C, which may be due to the condensation of hydroxyl groups. The DTA profiles for these glasses are consistent with [23,24]. On the basis of this observation, it is identified that endothermic peak appears between 95 and 120 C, which represents the glass transition (T g ).…”
Section: Thermal Analysissupporting
confidence: 61%
“…fraction, in which a "quenched [0.75Agi:0.25 AgC1] mixed system/solid solution" has been used as an alternate host in place of the traditional host salt AgI [8]. A number of glass/composite electrolytes have been discovered in the present laboratory using this alternate host which exhibits superior electrolyte properties than those prepared by the traditional host [9][10][11][12]. To identify the optimum conducting composition (OCC) the compositional dependence of conductivity (~) has been carried out using impedance spectroscopic technique.…”
Section: Introductionmentioning
confidence: 93%
“…[38] Silver molybdate in the triclinic (Ag 6 Mo 10 O 33 ) phase possesses a wide range of applications, including its use as a non-Pt electrocatalyst for oxygen reduction reactions, fast ion-conducting glass, electrodes in battery applications, etc. [39][40][41] Silver molybdate in triclinic structure consists of an unique arrangement of ions, in which a chain of Ag ions resides in-between MoO 6 octahedra or vice-versa. [24] For simplicity, the structure can be broken down into two basic units, one consisting of six octahedra sharing edges and another made of a square arrangement of four octahedra sharing edges.…”
Section: Doi: 101002/adma201601158mentioning
confidence: 99%